The Role of Source Credibility in the Validation of Information Depends on the Degree of (Im-)Plausibility. Issue 5 (3rd July 2021) - Wertgen, Andreas G.; Richter, Tobias; Rouet, Jean-François
ABSTRACT: This study examined the role of source credibility in the validation of factual information embedded in short narratives. In a self-paced reading experiment, we tested the assumption that the degree of (im-)plausibility determines the extent that source credibility affects validation during comprehension. We used reading times of target and spillover sentences and plausibility judgments as indicators of validation. Participants read stories with a high-credible versus low-credible person (expert versus nonexpert) who made plausible, somewhat implausible, or highly implausible assertions. Reading times increased and plausibility judgments varied as a function of knowledge consistency, decreasing from knowledge-consistent to implausible to knowledge-inconsistent items. Moreover, interactions of source credibility and plausibility were found for reading times of spillover sentences and plausibility judgments, indicating that source credibility and plausibility are jointly considered in validation. High-credible sources mitigated the perceived implausibility of somewhat implausible sentences but exacerbated the perceived implausibility of highly implausible information. A corresponding interactive pattern was found for the reading times of the spillover sentences. Thus, implicit and explicit indicators provided converging evidence that the modulating role of source credibility in validation depends on the degree of implausibility.